Analysis of Sharia-Based Governance in The Takaful Industry: A Review of Contemporary Literature - Muhammad Arifin Lubis; Asmaul Husna; Sella Kurnia Sari; Fauziah Hanum (PT. Maju Malaqbi Makkarana, 2026)
This study aims to explore and evaluate the development of studies on shariah-based governance in the takaful industry through a systematic literature review approach. Sharia governance has an important role in ensuring that all processes, policies, and operational activities of takaful companies are implemented in accordance with sharia regulations, while supporting the principles of transparency, accountability, fairness, and protection of participants' rights. This study uses the Systematic Literature Review (SLR) method by adopting the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. The databases used are Scopus and Google Scholar with the keywords